An evaluation of sports development work of national sports governing bodies in Uganda - Ayaa, Harriet (Πανεπιστήμιο Πελοποννήσου, 2024)
The purpose of the study is to present an evaluation of sports development work of national sports governing bodies in Uganda. It is generally objected to evaluate sports development work of national sports governing bodies in Uganda towards understanding the impact of and responses to COVID-19. It objects to describe sports development work of, assess impact of COVID-19 on sports development work and also describe measures adopted in response to COVID-19 by national sports governing bodies in Uganda. The study also intends to make recommendations based on results for solutions and future studies. The results show that perception of most sports development works drivers is generally positive with scattered negative views of certain facets of drivers.
Keywords: Αθλητισμός - Διοίκηση και οργάνωση - Ουγκάντα; Αθλητισμός και κράτος - Ουγκάντα; Αθλητικοί οργανισμοί - Ουγκάντα; Αθλητική διοίκηση - Ουγκάντα; Sports - Management - Uganda; Sports and state - Uganda; Sports organizations - Uganda; Sports administration - Uganda; Sports development work indices; National sports governing bodies; Impact; Responses; COVID-19; National Council of Sports; Uganda Olympic Committee